Students’ Motivation in Learning English - Fitri Rayani Siregar; Rahmadiny Siregar (English Education : English Journal for Teaching and Learning, 2020)
This study is to explore the students’ motivation in learning English. The kind of the research is quantitative research. The writer presented 40 items of questionnaire. Population of this research were the students at the sixth semester of English Department IAIN Padangsidimpuan (112) and the samples were 28 respondents that is taken by simple random sampling technique. The research is done by online. The data were taken by Google-Form or questionnaires trough Whats-App Group. Based on calculating the data, it was found that the highest scores was 172 and the lowest score was 122 . The mean score was  147, the median score was 149.7857 and the mode was 153.9. Students who has high motivation were 14.2% and medium were 64.2% and the students’ motivation who has low motivation were 21.4%. It concludes that the students’ motivation in learning English were medium category.